2013
DOI: 10.1177/0022022113513068
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Matrilineal and Patrilineal Kin Alloparental Effort to the Development of Life History Strategies and Patriarchal Values

Abstract: Childrearing behaviors are often shaped by familial and cultural principles that function as guides for socialization goals and effective childrearing practices. For an increasing number of Latino families, the extended kin often acts as a source of childcare support. Due to a scarcity of research on the familial support configurations of Latin American families, the current study utilizes a cross-cultural retrospective approach to explore the associations between matrilineal/ patrilineal kin and life history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…This means that slow LH strategists recall growing up in environments that were stable, prosocial, and cooperative. Follow-up retrospective research on Mexican and Costa Rican students (Cabeza de Baca et al, 2014) also found that slow LH strategists reported higher levels of positive family emotional climate, consistent with the previous study. Additionally, slow LH strategists reported lower levels of parental harshness.…”
Section: Theoretical Concerns and Conceptual Clarificationssupporting
confidence: 86%
See 2 more Smart Citations
“…This means that slow LH strategists recall growing up in environments that were stable, prosocial, and cooperative. Follow-up retrospective research on Mexican and Costa Rican students (Cabeza de Baca et al, 2014) also found that slow LH strategists reported higher levels of positive family emotional climate, consistent with the previous study. Additionally, slow LH strategists reported lower levels of parental harshness.…”
Section: Theoretical Concerns and Conceptual Clarificationssupporting
confidence: 86%
“…While the HKSS has been applied in only 12 studies to date, as noted in the critique, research on the Arizona Life History Battery (and its Short Form, the Mini-K), has produced quite a number of cross-cultural studies in recent years in geographically diverse places such as Chile, Costa Rica, Israel, Mexico, Poland, Singapore, Sweden, the Netherlands, and the United Kingdom (e.g., Abed et al, 2012; Buunk and Hoben, 2013; Buunk, Pollet, Klavina, Figueredo, and Dijkstra, 2009; Cabeza de Baca, Figueredo, and Ellis, 2012; Cabeza de Baca, Sotomayor-Peterson, Smith-Castro, and Figueredo, 2014; Egan et al, 2005; Figueredo et al, 2011; Figueredo, Cabeza de Baca, et al, 2013; Figueredo, Tal, McNeill, and Guillén, 2004; Figueredo and Wolf, 2009; Frías-Armenta et al, 2005; Frías-Armenta, Valdez-Ramirez, Nava-Cruz, Figueredo, and Corral-Verdugo, 2010; Gaxiola-Romero and Frías-Armenta, 2008; Jonason, Li, and Czarna, 2011; Sotomayor-Peterson, Cabeza de Baca, Figueredo, and Smith-Castro, 2012; Sotomayor-Peterson, Figueredo, Hendrickson-Christensen, and Taylor, 2012; Tal, Hill, Figueredo, Frías-Armenta, and Corral-Verdugo, 2006; Tifferet, Agrest, Shlomo Benisti, 2011; van der Linden, Figueredo, de Leeuw, Scholte, and Engels, 2012; Woodley of Menie and Madison, 2015). …”
Section: Theoretical Concerns and Conceptual Clarificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not imply that student samples represent the general population in every way; rather it implies that the levels of the criterion variable are comparable on the two most important dimensions for the sampling frame. As stated more eloquently by Cabeza de Baca and colleagues (2014), in relation to the qualified predictive validity of this practice when interpreted correctly:…”
Section: Discussionmentioning
confidence: 94%
“…Step 2 assessed measured maternal sensitivity, as environmental unpredictability creates competing interests for parents raising offspring under these conditions (Belsky, Schlomer, & Ellis, 2012). Given the significant impact of parental investment on offspring developmental outcomes (Cabeza de Baca & Ellis, 2017; Cabeza de Baca, Figueredo, & Ellis, 2012; Cabeza de Baca, Sotomayor-Peterson, Smith-Castro, & Figueredo, 2014; Cabeza de Baca, Sotomayor-Peterson, & Figueredo, 2017; Cabeza de Baca, Wahl, Bartnett, Figueredo, & Ellis, 2016; Sotomayor-Peterson, Cabeza de Baca, Figueredo, & Smith-Castro, 2012), our cascade model measured maternal sensitivity along three dimensions following Belsky et al’s (2012) work: (1) supportive presence, (2) respect for autonomy, and (3) hostility.…”
Section: Description Of Major Constructsmentioning
confidence: 99%